The Use of Neoclassical Economic Theory in the Analysis of Spanish-American Colonial Society. New Kingdom of Granada, XVI-XVIII Centuries. Unactual Reflections (2023)
The main title summarizes the purpose of this text, as it addresses a broad issue within historical research. It does so by delving into specific propositions put forth by the Colombian historian Germán Colmenares (1938-1990) regarding the application of neoclassical theory in the study of colonial society's economic history. These propositions appear to retain their validity. This analysis adopts a historiographical perspective that primarily focuses on the practical utilization of the concepts introduced in the examination. This perspective operates within a framework that perceives the historical discipline as inherently linked to other social sciences.